Pemanfaatan Citra Side Scan Sonar untuk Identifikasi Objek Bawah Laut - Prayetno, Eko; Ulinnuha, Hilmiyati (Universitas Gadjah Mada, 2020)
Lamong Bay waters are part of the Port of Tanjung Perak Surabaya. This port is included in one of the busiest ports in Indonesia. Therefore, a study is needed on the condition of the bottom waters and underwater infrastructure buildings to provide information on the safety of the shipping lanes and the landing of the lego anchor on the position of the underwater infrastructure. This study involves exploration activities such as the detection and sweeping of objects at the bottom of the sea and taking sediment samples using side scan sonar instruments and van veen grab sampler. This activity aims to identify the condition of objects of sea cables and pipelines in the waters of the Lamong Bay waters, evaluating the rules of immersion of submarine cables and pipelines in accordance with the Minister of Transportation Regulation No. PM 129 of 2016. The results of this activity will be in the form of a map of sea cables and sea pipes which will be attached to the Lamong Bay Field Painting Sheet. The submarine cable target recorded is in Line A with the cable target detected 2 (two) cable lines. Whereas the sea pipe is located at Lane B. The results of the inspection are to be placed on the Indonesian Sea Map No. 84 to determine the position of sea cables and Â pipelines. Each of the submarine cable and pipelines target was analyzed by Minister of Transportation Regulation No. PM 129 of 2016 concerning the regulation of immersion of underwater buildings. The results of the submarine cable and pipelines analysis have met the installation standards even though they are at a shallow depth. This suitability is seen based on dictum 2 (two) rules of burial that burials do not apply to the position of the underwater buildings crossing each other.